KEPASTIAN HUKUM SERTA PERTANGGUNGJAWABAN NOTARIS ATAS JANJI YANG TERCANTUM DALAM COVERNOTE TERHADAP PIHAK-PIHAK DALAM TRANSAKSI KREDIT PERBANKAN - Meliantha, Vania; Deni, Fitra (PALAR (Pakuan Law review), 2024)
Abstract Notary services are trusted by banks in carrying out credit commitments. After signing the credit agreement, the next step is for the bank to ask the Notary to make a covernote. Covernote is a statement made by a Notary stating that the deeds are still in process and the ability to assist the parties in the process of registering land rights until the certificate is issued within the time period determined by the Notary. In fact, it is not certain that the Notary will complete the documents he creates on time. So, when publishing a covernote, the Notary is responsible for the quality of the covernote he or she makes. This relates to Notaries complying with UUJN and the Notary's code of ethics. The issues discussed are the responsibility of the Notary for the promises contained in the covernote to the parties in the banking credit transaction and the legal certainty of the covernote made by the Notary to the parties in the banking credit transaction. This type of research is normative juridical, using literature study, namely secondary data collection. The results of the research are that if the Notary is not careful in carrying out his duties, the Notary will harm himself and related parties such as debtors, creditors or BPN. Responsibility of a Notary If the covernote is not in accordance with the existing facts, he/she can be held accountable, namely criminal, civil and ethical/administrative code. A covernote is simply a statement issued by a Notary as a reference for creditors where the contents of the covernote explain the processing of deeds or guarantees which are still in process and will be completed within the time period determined by the Notary, so that the covernote has no legal certainty. In the UUJN there is not a single article that regulates the authority of a Notary in issuing covernotes, so the covernote is not an authentic deed or a private deed. Keywords : Covernote, Notary Liability, Credit Disbursement. Abstrak Jasa Notaris dipercaya oleh bank dalam melakukan pengikatan kredit. Setelah ditandatangani perjanjian kredit, langkah selanjutnya pihak bank meminta Notaris untuk membuat covernote. Covernote adalah surat keterangan yang dibuat oleh Notaris menyatakan kepengurusan akta-akta masih dalam proses dan kesanggupan membantu para pihak untuk proses pendaftaran hak atas tanah sampai keluarnya sertifikat sesuai jangka waktu yang telah ditentukan oleh Notaris. Padahal, belum tentu Notaris akan menyelesaikan dokumen-dokumen yang dibuatnya tepat waktu. Sehingga, Notaris dalam menerbitkan covernote memiliki tanggungjawab atas kesanggupan covernote yang dibuatnya. Hal ini berkaitan dengan Notaris patut kepada UUJN dan kode etik Notaris. Permasalahan yang dibahas adalah pertanggungjawaban Notaris atas janji-janji yang tercantum dalam covernote terhadap para pihak dalam transaksi kredit perbankan dan kepastian hukum covernote yang dibuat oleh Notaris terhadap pihak dalam transaksi kredit perbankan. Jenis penelitian ini adalah yuridis normatif, dengan menggunakan studi kepustakaan yaitu dengan pengumpulan data sekunder. Hasil penelitian bila Notaris tidak berhati-hati melakukan tugasnya, Notaris akan merugikan dirinya sendiri dan pihak-pihak yang berkaitan seperti debitur, kreditur, ataupun BPN. Pertanggungjawaban Notaris jika membuat covernote tidak sesuai dengan fakta yang ada, maka dapat dimintakan pertanggungjawabannya yaitu secara pidana, perdata dan kode etik/ administratif. Covernote hanyalah surat keterangan yang dikeluarkan oleh Notaris sebagai pegangan kreditur dimana isi covernote menjelaskan pengurusan akta-akta ataupun jaminan yang masih dalam proses dan akan diselesaikan dalam jangka waktu yang telah ditentukan oleh Notaris, sehingga covernote tidak memiliki kepastian hukum. Dalam UUJN tidak ada satupun pasal yang mengatur mengenai kewenangan Notaris dalam menerbitkan covernote, sehingga covernote bukanlah merupakan akta otentik ataupun akta dibawah tangan. Kata Kunci : Covernote, Pertanggungjawaban Notaris, Pencairan Kredit.